3D printing resin material and method for 3D printing dental hard jaw pad using same
By introducing multiple curing closed polyurethane acrylate resin and high-performance acrylate monomers into 3D printing materials, combined with nano-silica fillers, the problems of low molding accuracy and poor wear resistance in the production of dental hard jaw pads are solved, and a high-strength, tear and wear-resistant dental hard jaw pads are achieved.
Patent Information
- Application Number
- CN202411947790.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing 3D printing materials have problems such as low molding accuracy, poor wear resistance, and cannot take into account strength and toughness, and poor tear resistance when making dental hard jaw pads, which cannot meet the application needs of dental hard jaw pads.
Multi-curing closed polyurethane acrylate resin is used, and acrylate monomer containing hydroxyl or carboxyl groups and/or acrylamide monomers and acrylate resins with high toughness and high Tg are printed through a 3D printer. Nanosilicon dioxide is used as fillers to print a dental hard jaw pad with excellent performance.
It realizes the high strength, high modulus, excellent tear resistance and wear resistance of dental hard jaw pads, while taking into account low water absorption, low solubility and high biocompatibility, meeting the high performance needs of dental hard jaw pads.
Smart Images

Figure BDA0005216525010000021 
Figure BDA0005216525010000031 
Figure BDA0005216525010000047
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing materials, and in particular to a 3D printing resin material and a method for 3D printing a dental hard jaw pad using the same. Background Art
[0002] In recent years, with the popularization of 3D printing digital light processing technology (Digital lightprocessing, DLP), the application area is also constantly expanding. At the same time, with the expansion of the types and scope of national medical device centralized procurement, 3D printing technology has also attracted much attention in the field of medical devices, especially in the field of dental diagnosis and treatment. The personalized, differentiated, and high-precision dental needs are perfectly matched with 3D printing technology. At present, the application of 3D printing technology in dentistry mainly includes surgical guides, dental restoration work models, temporary crowns, bridges, denture bases, etc. In addition, more requirements are put forward for the types and properties of materials. Among them, 3D printing of dental hard jaw pads has also achieved certain development, mainly to consolidate the retainers after the correction of dental malocclusion, and to treat jaw pads for temporomandibular joint disorders.
[0003] However, the current mainstream method of 3D printing hard jaw pads is that the clinic obtains the patient's tooth data through a dental scanner, and then transmits the data to the dental processing factory, which prints the corresponding tooth model with a printer, and then uses a certain thickness of PETG / TPU film material to heat and blister the 3D printed mold model. This process is an indirect production process using 3D printing technology, with large material loss, complex production process and long cycle.
[0004] Using 3D printing technology to directly print dental jaw pads can greatly improve the production efficiency of jaw pads, further simplify the production process, and reduce material loss during the production process, thereby further reducing production costs. At the same time, directly printing jaw pads can directly design jaw pads with customized thickness in local areas through design software, which provides a better diagnosis and treatment experience. However, hard jaw pads are required to have high strength, high modulus, excellent tear resistance, wear resistance, low water absorption value, solubility value, and excellent biocompatibility. The material technology is difficult, and there is currently a lack of products for direct 3D printing of hard jaw pads in China.
[0005] In addition, the existing 3D printing material system has problems such as low molding accuracy, poor wear resistance, inability to balance strength and toughness, and poor tear resistance, and cannot meet the application requirements of dental hard jaw pads. Summary of the invention
[0006] The purpose of the present invention is to develop a 3D printable dental hard jaw pad with excellent biocompatibility (cell survival rate greater than 90%), high strength (yield stress greater than 40MPa), yield strain greater than 4%, high modulus (tensile elastic modulus greater than 1600MPa), excellent tear resistance (right-angle tear strength greater than 100kN / m), wear resistance (wear resistance mass loss less than 0.25g / 1000r), low water absorption value (water absorption less than 32μg / mm 3 ), solubility value (solubility less than 1.6μg / mm 3 ).
[0007] To achieve the above purpose, the present invention introduces multi-cured blocked polyurethane acrylates into the materials used for 3D printing of dental hard jaw pads, and resins containing both photocuring groups and heat curing groups, further improving the degree of reaction. At the same time, blocked polyurethane acrylates improve the stability of the resin. In addition, acrylate monomers and / or acrylamide monomers containing hydroxyl or carboxyl groups and acrylic resins with high toughness and high Tg are introduced, and nano-silica is used as a filler to further improve the wear resistance of the 3D printed materials, while taking into account high transparency (transmittance greater than 85%).
[0008] Specifically, the purpose of the present invention is achieved through the following technical solutions: providing a
[0009] A 3D printing resin material, comprising the following raw materials in parts by weight:
[0010] 5-50 parts of multi-cured blocked polyurethane acrylate, preferably 30 parts;
[0011] 5-50 parts of acrylic resin, preferably 20 parts;
[0012] 15-55 parts of acrylamide monomer and / or acrylate monomer containing hydroxyl or carboxyl group, preferably 40 parts;
[0013] 1-4 parts of initiator, preferably 2 parts;
[0014] 0.01-2 parts of absorbent, preferably 0.1 parts;
[0015] 0.5-3 parts of nano silicon dioxide, preferably 1.5 parts;
[0016] The multi-cured blocked polyurethane acrylate is prepared by mixing a diol and an isocyanate in the presence of a catalyst at 60-90° C., and then adding 2-(tert-butylamino)ethyl methacrylate to continue mixing and reacting for end-capping; the catalyst is selected from one or more of an organic zinc catalyst and an organic bismuth catalyst.
[0017] Preferably, the multi-cured blocked polyurethane acrylate is prepared by the following raw material components:
[0018]
[0019] Preferably, the diol is selected from one or more of polyethylene glycol (PEG), polypropylene glycol (PPG), dimethyl hydroxy silicone oil, hydroxyl-terminated polybutadiene, and hydroxyl-terminated polybutylene adipate.
[0020] Preferably, the isocyanate is selected from one or more of hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane-4,4'-diisocyanate (HMDI).
[0021] In some specific embodiments, the catalyst is one or more of environmentally friendly organic zinc and organic bismuth catalysts, such as BCAT-E16, BCAT-E20, BCAT-E25A, BCAT-E28A, BCAT-T100R, BCAT-E20CX, ZCAT-EY18, ZCAT-EZ22, ZCAT-T50, BX-EM14, and BX-EM23 of Guangzhou Yourun Synthetic Materials Co., Ltd.
[0022] Preferably, the multi-cured blocked polyurethane acrylate is prepared by mixing a diol and an isocyanate, adding a catalyst, mixing for 3-7 hours at a temperature of 60-90°C and a shear line speed of 10-25 m / s, and then adding 2-(tert-butylamino)ethyl methacrylate and mixing for 2-4 hours for end-capping to obtain the multi-cured blocked polyurethane acrylate.
[0023] In one specific embodiment, the raw materials and preparation of the multi-cure blocked polyurethane acrylate are as follows.
[0024] raw material:
[0025]
[0026] Preparation: After PEG-800 and diphenylmethane diisocyanate are mixed, BX-EM23 is added, and the mixture is stirred at 80°C and a shear speed of 15 m / s for 4 hours. Then, 2-(tert-butylamino)ethyl methacrylate is added and stirred for 3 hours to obtain a multi-cured blocked polyurethane acrylate.
[0027] Preferably, the acrylic resin is selected from (meth) acrylic resins with high toughness (elongation at break>10%) and high Tg (Tg greater than 50°C), and can be specifically selected from CN1963NS, CN1964NS, CN1993CG, CN2920, CN2921, CN310NS, CN3211, CN8003NS, CN8010NS, CN8881NS, CN8883NS, CN8887NS, CN8889NS, CN8890NS, CN8891NS, CN8896NS, CN9001NS, CN9011, CN9014NS, CN9021 NS, CN9062, CN959, CN9290, CN959, CN964NS, CN969NS, CN983NS, CN991NS, one or more of Dymax's BR-930D, BR-941D, BR-952, BR-970BT, BR-970H, BR-990, BR-372, BR-571, BR-741, BR-744BT, BR-744SD, BR-742MS, BR-345, BR-374, BR-541S, BR-571, BR-582I10, BR-202, BR-541MB, BR-571MB.
[0028] Preferably, the acrylamide monomer and / or the acrylate monomer containing a hydroxyl group or a carboxyl group is selected from one or more of cyclotrimethylolpropane formal acrylate, acrylic acid, isobornyl methacrylate, isobornyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, (2) ethoxylated bisphenol A dimethacrylate, (4) ethoxylated bisphenol A dimethacrylate, (6) ethoxylated bisphenol A dimethacrylate, tricyclodecane dimethanol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, 4-acryloylmorpholine, dimethylaminopropyl acrylamide, diethyl acrylamide, N-hydroxyethyl acrylamide, and N,N-dimethylacrylamide.
[0029] Preferably, the initiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)-diphenylphosphine oxide, (2,4,6-trimethylbenzoyl)-phenylphosphonic acid ethyl ester, camphorquinone, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
[0030] Preferably, the absorbent is selected from at least one of triazine ultraviolet absorbers and benzophenone ultraviolet absorbers. In some specific embodiments, the triazine ultraviolet absorber can be selected from 2-[4,6-bis(2,4-xylyl)-1,3,5-triazine-2-yl]-5-(octyloxy)phenol (UV-1164), 2-(4,6-diphenyl-1,3,5-triazine-2)-5-n-hexaneoxy (UV-1577), UV1990 (Eutec Chemical), etc. and their derivatives; the benzophenone ultraviolet absorber can be selected from 2-hydroxy-4-n-octyloxybenzophenone (UV-531), 2,4-dihydroxybenzophenone (UV-O), 2-hydroxy-4-methoxybenzophenone (UV-9), etc. and any one or more of their derivatives.
[0031] Preferably, the nano-silicon dioxide has a particle size of 3-100 nanometers and is selected from Evonik 200V, 300, 380, 805, E812, Any one or more of E972.
[0032] In a specific embodiment, the 3D printing resin material comprises the following raw materials in parts by weight:
[0033]
[0034]
[0035] The present invention also provides a method for 3D printing a dental hard jaw pad, comprising the following steps:
[0036] Mix the above-mentioned 3D printing resin materials evenly according to weight;
[0037] The three-dimensional mechanical test model was printed by 3D printer, with a wavelength of 200-800nm and a radiation brightness of 20-100mw / cm 2 , cure at 40-60°C for 5-30 minutes, and then heat treat at 80-130°C for 1-3 hours.
[0038] In some specific embodiments, the method for 3D printing a dental hard jaw pad comprises the following steps:
[0039] Add the raw materials of the above-mentioned 3D printing resin material into the stirring and dispersing kettle in sequence, adjust the rotation speed to 500-2000r / min, that is, provide a shear line speed of 10-25m / s, control the temperature to 30-70°C (preferably 50°C), and stir and disperse for 2-6h (preferably 4h);
[0040] The three-dimensional mechanical test model was printed by 3D printer, cleaned with 75% medical alcohol, blown dry with compressed air gun, and then tested at 200-800nm wavelength (preferably 405nm), 20-100mw / cm 2 (Preferably 50mw / cm 2 ), and curing in a curing box at 40-60°C (preferably 50°C) for 5-30 minutes (preferably 10 minutes), and then heat-treating in an oven at 80-130°C (preferably 110°C) for 1-3 hours (preferably 2 hours).
[0041] The 3D printing resin material of the present invention introduces multiple cured closed polyurethane acrylates to improve the reaction degree and stability of the resin, and is combined with acrylate monomers and / or acrylamide monomers containing hydroxyl or carboxyl groups and acrylic resins with high toughness and high Tg, and nano-silica fillers, so that the printing speed is fast, the wear resistance of the 3D printed material can be further improved, and high transparency is also taken into account.
[0042] The dental hard jaw pad made by 3D printing of the 3D printing resin material of the present invention has excellent biocompatibility (cell survival rate greater than 90%), high strength (yield stress greater than 40MPa), yield strain greater than 4%, high modulus (tensile elastic modulus greater than 1600MPa), excellent tear resistance (right-angle tear strength greater than 100kN / m), wear resistance (wear resistance mass loss less than 0.25g / 1000r), low water absorption value (water absorption rate less than 32μg / mm 3 ), solubility value (solubility less than 1.6μg / mm 3 ), while taking into account high transparency (light transmittance greater than 85%). DETAILED DESCRIPTION
[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0045] The term "and / or" as used in the specification and appended claims refers to and includes any and all possible combinations of one or more of the associated listed items.
[0046] Example 1
[0047] Preparation of multi-cured blocked polyurethane acrylate: After mixing 63 parts of PEG-800 and 40 parts of diphenylmethane diisocyanate (MDI) by weight, 0.1 parts of BX-EM23 were added, and the mixture was stirred at 80°C and a shear speed of 15 m / s for 4 hours. Then, 30 parts of 2-(tert-butylamino)ethyl methacrylate were added for end-capping, and stirring was continued for 3 hours to obtain multi-cured blocked polyurethane acrylate.
[0048] Preparation of 3D printing resin material: by weight, 30 parts of multi-cured blocked polyurethane acrylate, 20 parts of BR-952, 20 parts of diethyl acrylamide, 20 parts of hydroxyethyl methacrylate, 2 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 0.05 parts of 2- (4,6-diphenyl-1,3,5-triazine-2) -5-n-hexane oxide (UV-1577), 1.5 parts of 380 were added into the stirring and dispersing kettle in sequence, the rotation speed was adjusted to 1000 r / min, the temperature was controlled at 50 °C, and the mixture was stirred and dispersed for 4 h to obtain the 3D printing resin material.
[0049] 3D printed dental hard jaw pad: The 3D printing resin material is used to print out a three-dimensional mechanical test model of the dental hard jaw pad through a 3D printer, cleaned with 75% medical alcohol, blown dry with a compressed air gun, and then heated at a wavelength of 405nm and 50mw / cm 2 , and cured in a curing box at 50°C for 10 minutes, and then heat treated in an oven at 110°C for 2 hours to obtain the dental hard jaw pad of Example 1.
[0050] Example 2
[0051] Preparation of multi-cured blocked polyurethane acrylate: After mixing 55 parts of dimethylhydroxy silicone oil and 35 parts of hexamethylene diisocyanate (HDI) by weight, 0.05 parts of BCAT-E20 were added, and the mixture was stirred at 60°C and a shear speed of 10 m / s for 7 hours, and then 25 parts of 2-(tert-butylamino)ethyl methacrylate were added for end-capping. After continuing to stir for 2 hours, multi-cured blocked polyurethane acrylate was obtained.
[0052] Preparation of 3D printing resin material: by weight, 5 parts of multi-cured blocked polyurethane acrylate, 5 parts of CN1963NS, 5 parts of N-hydroxyethyl acrylamide, 10 parts of isobornyl acrylate, 1 part of (2,4,6-trimethylbenzoyl)-phenylphosphonic acid ethyl ester, 0.01 parts of 2-hydroxy-4-n-octyloxybenzophenone (UV-531), 0.5 parts of E812 was added into the stirring and dispersing kettle in sequence, the rotation speed was adjusted to 500 r / min, the temperature was controlled at 30°C, and the mixture was stirred and dispersed for 6 hours to obtain the 3D printing resin material.
[0053] 3D printed dental hard jaw pad: The 3D printing resin material is used to print out a three-dimensional mechanical test model of the dental hard jaw pad through a 3D printer, cleaned with 75% medical alcohol, blown dry with a compressed air gun, and then heated at a wavelength of 200nm and 100mw / cm 2 , and cured in a curing box at 60°C for 5 minutes, and then heat treated in an oven at 80°C for 3 hours to obtain the dental hard jaw pad of Example 2.
[0054] Example 3
[0055] Preparation of multi-cured blocked polyurethane acrylate: After mixing 65 parts of hydroxyl-terminated polybutylene adipate and 45 parts of xylene diisocyanate (XDI) by weight, 0.3 parts of ZCAT-EY18 were added, and the mixture was stirred at a shear speed of 25 m / s at 90°C for 3 hours, and then 35 parts of 2-(tert-butylamino)ethyl methacrylate were added for blocking. After continuing to stir for 4 hours, multi-cured blocked polyurethane acrylate was obtained.
[0056] Preparation of 3D printing resin material: According to weight, 50 parts of multi-cured blocked polyurethane acrylate, 50 parts of CN9021NS, 30 parts of N,N-dimethylacrylamide, 25 parts of (2) ethoxylated bisphenol A dimethacrylate, 4 parts of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2 parts of 2-hydroxy-4-methoxybenzophenone (UV-9), 3 parts of E812 was added into the stirring and dispersing kettle in sequence, the rotation speed was adjusted to 2000 r / min, the temperature was controlled at 70°C, and the mixture was stirred and dispersed for 2 h to obtain the 3D printing resin material.
[0057] 3D printed dental hard jaw pad: The 3D printing resin material is used to print out a three-dimensional mechanical test model of the dental hard jaw pad through a 3D printer, cleaned with 75% medical alcohol, blown dry with a compressed air gun, and then heated at a wavelength of 800nm and 20mw / cm 2 The resultant was cured in a curing box at 40°C for 30 minutes, and then heat treated in an oven at 130°C for 1 hour to obtain the dental hard jaw pad of Example 3.
[0058] Example 4
[0059] Preparation of multi-cured blocked polyurethane acrylate: After mixing 60 parts of polypropylene glycol, 20 parts of isophorone diisocyanate (IPDI) and 20 parts of toluene diisocyanate (TDI) by weight, 0.2 parts of BCAT-E28A were added, and the mixture was stirred at 70°C and a shear speed of 20 m / s for 5 hours, and then 32 parts of 2-(tert-butylamino)ethyl methacrylate were added for end-capping. After continuing to stir for 3 hours, multi-cured blocked polyurethane acrylate was obtained.
[0060] Preparation of 3D printing resin material: According to weight, 20 parts of multi-cured blocked polyurethane acrylate, 45 parts of BR-952, 40 parts of isobornyl acrylate, 2 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 0.05 parts of 2,4-dihydroxybenzophenone (UV-O), 1.5 parts of 380 were added into the stirring and dispersing kettle in sequence, the rotation speed was adjusted to 1000 r / min, the temperature was controlled at 50 °C, and the mixture was stirred and dispersed for 4 h to obtain the 3D printing resin material.
[0061] 3D printed dental hard jaw pad: The 3D printing resin material is used to print out a three-dimensional mechanical test model of the dental hard jaw pad through a 3D printer, cleaned with 75% medical alcohol, blown dry with a compressed air gun, and then heated at a wavelength of 405nm and 50mw / cm 2 , and cured in a curing box at 50°C for 10 minutes, and then heat treated in an oven at 110°C for 2 hours to obtain the dental hard jaw pad of Example 4.
[0062] Example 5
[0063] Preparation of multi-cured blocked polyurethane acrylate: After mixing 58 parts of methylhydroxy silicone oil and 42 parts of xylene diisocyanate (XDI) by weight, 0.1 parts of BCAT-T100R were added, and the mixture was stirred at 80°C and a shear speed of 20 m / s for 4 hours, and then 28 parts of 2-(tert-butylamino)ethyl methacrylate were added for end-capping. After continuing to stir for 4 hours, multi-cured blocked polyurethane acrylate was obtained.
[0064] Preparation of 3D printing resin material: According to weight, 25 parts of multi-cured blocked polyurethane acrylate, 25 parts of CN8890NS, 35 parts of diethyl acrylamide, 2 parts of (2,4,6-trimethylbenzoyl)-phenylphosphonic acid ethyl ester, 0.05 parts of 2-hydroxy-4-methoxybenzophenone (UV-9), 1.5 parts of E812 was added into the stirring and dispersing kettle in sequence, the rotation speed was adjusted to 1000 r / min, the temperature was controlled at 50°C, and the mixture was stirred and dispersed for 4 hours to obtain the 3D printing resin material.
[0065] 3D printed dental hard jaw pad: The 3D printing resin material is used to print out a three-dimensional mechanical test model of the dental hard jaw pad through a 3D printer, cleaned with 75% medical alcohol, blown dry with a compressed air gun, and then heated at a wavelength of 405nm and 50mw / cm 2 , and cured in a curing box at 50°C for 10 minutes, and then heat treated in an oven at 110°C for 2 hours to obtain the dental hard jaw pad of Example 5.
[0066] During the research process, the present invention also explored jaw pads made by comparative examples of different formulations and process conditions, as follows.
[0067] Comparative Example 1
[0068] The preparation method of the jaw pad of Comparative Example 1 is different from that of Example 1 in that: in the preparation of the multi-cured blocked polyurethane acrylate, 2-(tert-butylamino)ethyl methacrylate is replaced with 2-hydroxyethyl methacrylate, and the other process steps are the same as those of Example 1.
[0069] Comparative Example 2 (reaction temperature is too low)
[0070] The preparation method of the jaw pad in Comparative Example 2 is different from that in Example 1 in that: in the preparation of the multi-cured blocked polyurethane acrylate, after adding BX-EM23, stirring is carried out at a temperature of 50°C, and the other process steps are the same as those in Example 1.
[0071] Comparative Example 3 (Multiple Curing Blocked Polyurethane Acrylate Content Too High)
[0072] The difference between the preparation method of the jaw pad of Comparative Example 3 and that of Example 1 is that in the preparation of the 3D printing resin material, the addition amount of the multi-curing blocked polyurethane acrylate is 60 parts, and the other process steps are the same as those of Example 1.
[0073] Comparative Example 4 (without adding acrylic resin)
[0074] The preparation method of the jaw pad of Comparative Example 4 is different from that of Example 1 in that BR-952 is not added in the preparation of the 3D printing resin material, and the other process steps are the same as those of Example 1.
[0075] Comparative Example 5 (Acrylic Acid Resin Content Too High)
[0076] The preparation method of the jaw pad of Comparative Example 5 is different from that of Example 1 in that: in the preparation of the 3D printing resin material, the addition amount of BR-952 is 60 parts, and the other process steps are the same as those of Example 1.
[0077] Comparative Example 6 (Content of acrylamide monomer and / or acrylate monomer containing hydroxyl or carboxyl group is too low)
[0078] The preparation method of the jaw pad of Comparative Example 6 is different from that of Example 1 in that: in the preparation of the 3D printing resin material, the added amount of diethyl acrylamide is 5 parts, and the added amount of hydroxyethyl methacrylate is 5 parts, and the other process steps are the same as those of Example 1.
[0079] Comparative Example 7 (Content of acrylamide monomer and / or acrylate monomer containing hydroxyl or carboxyl group is too high)
[0080] The preparation method of the jaw pad of Comparative Example 7 is different from that of Example 1 in that: in the preparation of the 3D printing resin material, the added amount of diethyl acrylamide is 30 parts, and the added amount of hydroxyethyl methacrylate is 30 parts, and the other process steps are the same as those of Example 1.
[0081] Comparative Example 8 (without adding nano silicon dioxide)
[0082] The difference between the preparation method of the jaw pad in comparative example 8 and that in embodiment 1 is that: in the preparation of the 3D printing resin material, no 380, other process steps are the same as those in Example 1.
[0083] Comparative Example 9 (Nano-silicon dioxide content is too high)
[0084] The preparation method of the jaw pad in Comparative Example 9 is different from that in Example 1 in that: in the preparation of the 3D printing resin material, The addition amount of 380 is 5 parts, and the other process steps are the same as those in Example 1.
[0085] Comparative Example 10 (2-(tert-butylamino)ethyl methacrylate content is too high)
[0086] The difference between the preparation method of the jaw pad in Comparative Example 10 and that in Example 1 is that in the preparation of the multi-cured blocked polyurethane acrylate, the added amount of 2-(tert-butylamino)ethyl methacrylate is 45 parts, and the other process steps are the same as those in Example 1.
[0087] Comparative Example 11 (2-(tert-butylamino)ethyl methacrylate content is too low)
[0088] The difference between the preparation method of the jaw pad of Comparative Example 11 and that of Example 1 is that in the preparation of the multi-cured blocked polyurethane acrylate, the added amount of 2-(tert-butylamino)ethyl methacrylate is 15 parts, and the other process steps are the same as those of Example 1.
[0089] Comparative Example 12 (MDI content is too high)
[0090] The difference between the preparation method of the jaw pad in Comparative Example 12 and that in Example 1 is that in the preparation of the multi-cured blocked polyurethane acrylate, the amount of MDI added is 55 parts, and the other process steps are the same as those in Example 1.
[0091] Comparative Example 13 (MDI content is too low)
[0092] The difference between the preparation method of the jaw pad in Comparative Example 13 and that in Example 1 is that in the preparation of the multi-cured blocked polyurethane acrylate, the amount of MDI added is 25 parts, and the other process steps are the same as those in Example 1.
[0093] The jaw pads obtained in the embodiments and comparative examples 1-13 were subjected to performance tests, and the test methods and results are shown in Table 1.
[0094] Table 1 Jaw pad performance test results of Examples and Comparative Examples 1-13
[0095]
[0096]
[0097] From the test results in Table 1, it can be seen that the dental hard jaw pads of Examples 1-5 using the technical solution of the present invention have a yield stress of more than 40 MPa, a yield strain of more than 4%, a tensile elastic modulus of more than 1600 MPa, a right-angle tear strength of more than 100 kN / m, a wear resistance mass loss of less than 0.25 g / 1000 r, and a water absorption rate of less than 32 μg / mm 3 , solubility is less than 1.6μg / mm 3 The in vitro cytotoxicity (cell survival rate %) is greater than 90%, the light transmittance is greater than 85%, it has excellent biocompatibility, high strength, high modulus, excellent tear resistance, wear resistance, low water absorption value and solubility value, which meet the requirements of the dental hard jaw pad described in the present invention.
[0098] The test results of the jaw pad performance of comparative examples 1-13 show that the yield stress is less than 25MPa, the yield strain is less than 4%, the tensile elastic modulus is less than 700MPa, the right-angle tear strength is less than 100kN / m, the wear resistance mass loss is greater than 0.25g / 1000r, and the water absorption rate is greater than 32μg / mm 3 , solubility greater than 1.6μg / mm 3 , the transmittance is lower than 70%, and the in vitro cytotoxicity (cell survival rate %) is lower than 70%, which makes it unsuitable for use as a dental hard jaw pad.
[0099] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A 3D printing resin material, characterized in that: The invention comprises the following raw materials in parts by weight: 5-50 parts of multi-cured blocked polyurethane acrylate; 5-50 parts of acrylic resin; 15-55 parts of acrylamide monomer and / or acrylate monomer containing hydroxyl or carboxyl; 1-4 parts of initiator; 0.01-2 parts of absorbent; 0.5-3 parts of nano-silicon dioxide; The multi-cured blocked polyurethane acrylate is prepared by mixing a diol and an isocyanate in the presence of a catalyst at 60-90° C., and then adding 2-(tert-butylamino)ethyl methacrylate to continue mixing and reacting for end-capping; the catalyst is selected from one or more of an organic zinc catalyst and an organic bismuth catalyst.
2. The 3D printing resin material according to claim 1, characterized in that: The multi-cured blocked polyurethane acrylate is prepared by the following raw material components: 55-65 parts of diol, 35-45 parts of isocyanate, Catalyst 0.05-0.3 parts, 2-(tert-butylamino)ethyl methacrylate 25-35 parts.
3. The 3D printing resin material according to claim 1 or 2, characterized in that: The diol is selected from one or more of polyethylene glycol, polypropylene glycol, dimethyl hydroxy silicone oil, hydroxyl-terminated polybutadiene, and hydroxyl-terminated polybutylene adipate.
4. The 3D printing resin material according to claim 1 or 2, characterized in that: The isocyanate is selected from one or more of hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane-4,4'-diisocyanate.
5. The 3D printing resin material according to claim 1 or 2, characterized in that: The multi-cured blocked polyurethane acrylate is prepared by mixing diol and isocyanate, adding a catalyst, mixing for 3-7 hours at a temperature of 60-90° C. and a shear line speed of 10-25 m / s, and then adding 2-(tert-butylamino)ethyl methacrylate and mixing for 2-4 hours for end-capping.
6. The 3D printing resin material according to claim 1, characterized in that: The acrylic resin is selected from CN1963NS, CN1964NS, CN1993CG, CN2920, CN2921, CN310NS, CN3211, CN8003NS, CN8010NS, CN8881NS, CN8883NS, CN8887NS, CN8889NS, CN8890NS, CN8891NS, CN8896NS, CN9001NS, CN9011, CN9014NS, CN9021NS, CN9062, CN959, CN9290, C N959, CN964NS, CN969NS, CN983NS, CN991NS, one or more of Dymax's BR-930D, BR-941D, BR-952, BR-970BT, BR-970H, BR-990, BR-372, BR-571, BR-741, BR-744BT, BR-744SD, BR-742MS, BR-345, BR-374, BR-541S, BR-571, BR-582I10, BR-202, BR-541MB, BR-571MB.
7. The 3D printing resin material according to claim 1, characterized in that: The acrylamide monomer and / or acrylate monomer containing a hydroxyl group or a carboxyl group is selected from one or more of cyclotrimethylolpropane methylal acrylate, acrylic acid, isobornyl methacrylate, isobornyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, (2) ethoxylated bisphenol A dimethacrylate, (4) ethoxylated bisphenol A dimethacrylate, (6) ethoxylated bisphenol A dimethacrylate, tricyclodecane dimethanol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, 4-acryloylmorpholine, dimethylaminopropyl acrylamide, diethyl acrylamide, N-hydroxyethyl acrylamide, and N,N-dimethyl acrylamide.
8. The 3D printing resin material according to claim 1, characterized in that: The initiator is selected from one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)-diphenylphosphine oxide, (2,4,6-trimethylbenzoyl)-phenylphosphonic acid ethyl ester, camphorquinone, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
9. The 3D printing resin material according to claim 1, characterized in that: The absorber is selected from at least one of a triazine ultraviolet absorber and a benzophenone ultraviolet absorber.
10. A method for 3D printing a dental hard jaw pad, characterized in that: The following steps are involved: Mix the raw materials of the 3D printing resin material according to any one of claims 1 to 9 uniformly by weight; The three-dimensional mechanical test model was printed by 3D printer, with a wavelength of 200-800nm and a radiation brightness of 20-100mw / cm 2 , cure at 40-60°C for 5-30 minutes, and then heat treat at 80-130°C for 1-3 hours.
Citation Information
Patent Citations
Polyurethane resin having multiple mechanisms of hardening for use in producing three-dimensional objects
CN107077064A
Soft light-cured 3D printing resin material and preparation method thereof
CN111471139A
3D printing resin composition for shoe material, 3D printing product and preparation method of 3D printing product
CN115073674A
Photosensitive resin containing blocked polyurethane and application
CN117089025A
Self-repairing dual-curing photosensitive resin material and preparation method thereof
CN117624491A
Cited By
3D printing resin material and method for 3D-printing dental hard occlusal splint by using 3D printing resin material
WO2026138305A1